Effect of Fermentation of Cow Feces with Different Doses on Growth Rate (Chlorella sp) - Mukhlisin Mukhlisin; Netti Aryani; Nuraini Nuraini (Jurnal Akuakultur SEBATIN, 2024)
This research was conducted for 30 days in May 2022, at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine of Riau University. The a imed of this study to determine the effect of fertilizer application from fermented cow feces on the growth of Chlorella sp. and knowing the best dose of fermented cow feces for the growth of Chlorella sp. This study used an experimental method, while the experimental design used a completely randomized design with 4 treatments, each with 3 replications. as for the treatment in this study P0 (Walne fertilizer 1 ml//L), P1 (cow feces fermented 3.5 ml/L), P2 (fermented cow feces 5.5 ml/L), P3 (fermented cow feces 7.5 ml/L). The best fermented cow feces is 5.5 ml/L culture media with population density the highest was 340.00 x 104 cells/ml and the specific growth rate was 0.29 cells/day and the highest density peak occurred on the 9th day. Water quality during the study was in the optimum range, namely temperature with a value of 28.10C - 29.90C, pH during the study was 6-8 and DO 4 - 5.9 mg/L